AN ASSESSMENT OF GROWTH FOR EARLY SELECTING FAST-GROWING MELALEUCA HYBRIDS ON SEASONAL FLOODING AND SULPHATE ACID SOIL IN SOUTHERN VIETNAM - Vu Tho, Hoang (Journal of Forestry Science and Technology, 2016)
This paper presents the first published selection of hybrid Melaleuca species which is experimented in Southern Vietnam. Among 126 inter-specific crossing Melaleuca combinations, 27 hybrids with trunk volume with bark exceeding by more than 20% in comparison with either of their best parents have been selected at the just young stage. Additionally, 27 hybrids also perform an aggressive growth response to the harsh condition of seasonal flood and sulphate soil. The general combining ability (GCA) of V43 trees when crossing with others of M. leucadendra and M. cajuputi would almost ever give the hybrid offspring of positive heterosis on seasonal flooding and sulphate soil. Whereas the specific combining ability (SCA) of female parent tree Ca65 when crossing with L47 as male parent can create the hybrid combination Ca65L47 with the largest trunk volume at very young stage (3.65 dm3 per tree). There are 7 significant hybrid combinations including Ca65L47, L56Ca72, L42V43, Ca65V32, Ca65L60, L50V43, and L59V66 which are estimated to reach to 30 m3/ha/year of trunk productivity after 5 years old.